GPR65 is a novel immune biomarker and regulates the immune microenvironment in lung adenocarcinoma - Zhou, Hanxu; Chen, Zhi; Gao, Shuang; Lian, Chaoqun; Hu, Junjie; Lu, Jin; Zhang, Lei (Frontiers in Immunology, 2025)
BackgroundThe tumor microenvironment (TME) plays a crucial role in the progression of lung adenocarcinoma (LUAD), and it may serve as the best prognostic predictor of LUAD. GPR65 is an extracellular pH-sensing G protein-coupled receptor and a glycosphingolipid receptor, which is engaged in the functions of regulating tumor immunity. However, the prognostic value of GPR65 and its relevance to immune infiltration in LUAD are unknown.MethodsThe proportion of immune, stromal and tumor cells in LUAD samples was assessed by ESTIMATE algorithm scores with RNA sequence data and clinical information from LUAD patients downloaded from The Cancer Genome Atlas (TCGA) database. We screened differential genes (DEGs) in the immune and stromal components, and then screened modular genes by the WGCNA algorithm, which were intersected with DEGs and incorporated into the LASSO-COX regression model. Additionally, nomogram containing GPR65 and clinical features were constructed for predicting patient prognosis. Then, the correlation between GPR65 and immune cell infiltration was assessed by CIBERSORT, and the impact of hub gene on immunotherapy was determined using correlation analysis between GPR65 and immune checkpoint molecules. Finally, we confirmed the expression of GPR65 in LUAD by Western Blot, Quantitative Real-time PCR and Immunohistochemistry.ResultsIn our study, we found that low expression of GPR65 was associated with poorer overall survival and primary treatment outcome in patients with LUAD. Moreover, GPR65 expression was found to be closely correlated with multiple tumor infiltrating immune cells (TIICs) and immune checkpoint molecules. Immunohistochemistry and Quantitative Real-time PCR results confirmed that the transcription levels and protein expression levels of GPR65 in LUAD tissues were significantly lower than in normal tissues. Western Blot results showed that the expression of GPR65 in human normal lung epithelial cell lines was significantly higher than the expression level in LUAD cell lines.ConclusionsGPR65 may be an important immune biomarker in the prognosis and diagnosis of LUAD.